Crush-origin pseudotachylyte in granitic mylonites of continental exhumed Ailaoshan-Red River shear zone southeastern Asia. (June 2022) - Li, Wenyuan; Cao, Shuyun; Zhan, Lefan; Cheng, Xuemei; Li, Wei; Lyu, Meixia
Abstract: Tectonic pseudotachylytes have provided valuable insights into the evolution of seismic activity during crustal deformation. However, the origin and formation processes of pseudotachylytes are still debated. Thin pseudotachylyte veins were first recognized within the granitic mylonites of the continental exhumed Ailaoshan-Red River strike-slip shear zone, southeastern Asia, which record the deformation characteristics from ductile (mylonite) to brittle deformation (ultracataclasite). Mylonitization resulted in the recrystallization of quartz aggregates/ribbons, fine-grained plagioclase, and the concentration of biotite into biotite-rich foliation planes. The pseudotachylyte veins have various angles oblique to the host rock foliation, which record superimposition of the latter brittle deformation onto former ductile fabrics. Observations of the microstructure and quartz clast size distribution (obey power-law distribution) suggest that crushing was the dominant process in the formation of pseudotachylyte in the samples. Plagioclase within the pseudotachylyte vein presents a complex texture of high-strength nanocrystalline to partly amorphous material. Detailed microstructure observation revealed that amorphous materials form by a solid-state amorphization process and is different from friction melts. The changes in composition between plagioclase clasts and amorphous materials (enriched in Ca, but depleted in Na) provide evidence of mechanochemical effect that accompanies fault motion and comminution process. When a sufficient amount of amorphous material is formed, it has great significance in fault weakening through the coseismic slip of the strain partition. Highlights: Pseudotachylyte records overprint deformation of brittle to ductile. Plagioclase presents complex texture of nanocrystalline to partly amorphous material. Pseudotachylyte veins were mainly formed by fast crushing process.